2017
DOI: 10.1371/journal.pbio.2000931
|View full text |Cite
|
Sign up to set email alerts
|

A Ca2+ channel differentially regulates Clathrin-mediated and activity-dependent bulk endocytosis

Abstract: Clathrin-mediated endocytosis (CME) and activity-dependent bulk endocytosis (ADBE) are two predominant forms of synaptic vesicle (SV) endocytosis, elicited by moderate and strong stimuli, respectively. They are tightly coupled with exocytosis for sustained neurotransmission. However, the underlying mechanisms are ill defined. We previously reported that the Flower (Fwe) Ca2+ channel present in SVs is incorporated into the periactive zone upon SV fusion, where it triggers CME, thus coupling exocytosis to CME. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 60 publications
11
54
0
1
Order By: Relevance
“…Conventional presynaptic calcium imaging uses action-potential evoked stimulation to elicit presynaptic calcium influx through voltage gated calcium channels at active zones (Muller and Davis, 2012; Yao et al, 2017). This standard approach would be unlikely to specifically detect the calcium signal through DKaiR1D receptors for two reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional presynaptic calcium imaging uses action-potential evoked stimulation to elicit presynaptic calcium influx through voltage gated calcium channels at active zones (Muller and Davis, 2012; Yao et al, 2017). This standard approach would be unlikely to specifically detect the calcium signal through DKaiR1D receptors for two reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Some cargoes, such as VAMP4, are preferentially accumulated by ADBE, perhaps explaining why VAMP4 is also essential for this mode of endocytosis (Nicholson-Fish et al, 2015). Interestingly, the SV-associated calcium channel Flower, which is deposited into the plasma membrane during high activity, may provide calcium influx to trigger ADBE and thus facilitate the coupling of neuronal activity to ADBE (Yao et al, 2009(Yao et al, , 2017. Therefore, specific vesicle proteins may play direct roles in ADBE rather than being passively retrieved.…”
Section: Activity-dependent Bulk Endocytosismentioning
confidence: 99%
“…The receiving cells of the ASP require Synaptotagmin‐4 and the glutamate receptor GluRII. This is noteworthy given that Ca 2+ is a crucial regulator of endocytosis and neurotransmitter regulation . Huang et al further demonstrated that Ca 2+ transients observed in cytonemes correlate with Dpp uptake.…”
Section: Parallels Between Neurotransmission and Morphogen‐based Tranmentioning
confidence: 90%
“…This is noteworthy given that Ca 2+ is a crucial regulator of endocytosis and neurotransmitter regulation. [77][78][79] Huang et al further demonstrated that Ca 2+ transients observed in cytonemes correlate with Dpp uptake. This suggests that signal uptake and transport within cytonemes depends on local Ca 2+ concentrations.…”
Section: Parallels Between Neurotransmission and Morphogen-based Trmentioning
confidence: 97%
See 1 more Smart Citation